The effectiveness of problem-based learning assisted with the ethnomathematics-based Geocube e-module on problem-solving skills - Sumaji, Sumaji; Widianingrum, Evi; Wanabuliandari, Savitri; Premprayoon, Kasem (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2025)
Problem-solving skills are essential in improving the creative, critical, and logical thinking skills needed in mathematics learning and daily life. This study aims to examine the effectiveness of problem-based learning (PBL)-assisted ethnomathematics-based Geocube e-module on problem-solving skills. This quantitative research applied a quasi-experimental design. The specific design applied in this research is the non-equivalent pretest-posttest control group design. The research sample consisted of 32 participants, all of whom were students involved in this study. Research instruments included test questions. The researchers analysed the data using a two-sample t-test for independent samples and an N-gain test. The results showed that the application of the PBL learning model assisted by the Geocub e-module based on ethnomathematics effectively improved problem-solving skills. It can be seen that (1) the average mathematical problem-solving skills of students in the experimental class were better than the control class, (2) there is an increase in the average of students' mathematical problem-solving skills after being taught the PBL model assisted by the Geocub e-module based on ethnomathematics. The researchers concluded that the implementation of PBL, assisted with the ethnomathematics-based Geocub e-module, effectively improved the mathematics problem-solving skills of the students.